2012
DOI: 10.1021/ja305369u
|View full text |Cite
|
Sign up to set email alerts
|

p53 Searches on DNA by Rotation-Uncoupled Sliding at C-Terminal Tails and Restricted Hopping of Core Domains

Abstract: The tumor suppressor p53 is a transcription factor that searches its cognate sites on DNA. During the search, the roles and interplay of its two DNA binding domains, the folded core domain and the disordered C-terminal domain (CTD), have been controversial. Here, we performed molecular simulations of p53 at various salt concentrations finding that, at physiological salt concentration, p53 diffuses along nonspecific DNA via rotation-uncoupled sliding with its CTD, whereas the core domain repeats dissociation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
117
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 53 publications
(115 reference statements)
11
117
0
Order By: Relevance
“…In 50% of human cancers, the mutations of p53 gene are found, which are located in the core domain and prevent the specific binding to DNA [3]. Due to its importance, the mechanism by which p53 searches for its binding sites among huge DNA has been the focus of intensive investigations [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In 50% of human cancers, the mutations of p53 gene are found, which are located in the core domain and prevent the specific binding to DNA [3]. Due to its importance, the mechanism by which p53 searches for its binding sites among huge DNA has been the focus of intensive investigations [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is still highly controversial how p53 recognizes its specific target site on DNA. 6,15,[17][18][19] According to the previously reported data, G245, R248, and R249 residues on wild-type p53DBD might be able to form well-defined hydrogen bonds, and then R248 could interact with DNA at the minor groove properly.…”
mentioning
confidence: 87%
“…When bound to DNA, the p53 protein acts in different cis/trans interac ons with its target sequences, modula ng the transcrip on of various target genes [695,696]. Rela vely recently it was found that the p53 molecule may ac vely slide along the length of the DNA molecule, searching for its cognate control elements [697,698]. p53 is capable of ac va ng both the ini a on and the elonga on from promoters for RNA polymerase II, as it can bind directly to TFIIH [699,700].…”
Section: Irish Blessingmentioning
confidence: 99%